Cytomorphometric analysis of oral submucous fibrosis and leukoplakia using methyl green-pyronin Y, Feulgen staining and exfoliative brush cytology. (January 2015) - Metgud, R; Gupta, K; Prasad, U; Gupta, J
Abstract The incidence of potentially malignant oral pathology such as leukoplakia, oral submucous fibrosis and squamous cell carcinoma has increased in India. We investigated whether cytoplasmic diameter, nuclear diameter and nucleus:cytoplasm ratio in exfoliative cytology are reliable indicators of potentially malignant lesions. We also investigated methyl green-pyronin Y and Feulgen staining as simple time saving and cost effective staining techniques for diagnostic exfoliative cytology. Cell and nuclear diameters of squamous cells of normal buccal mucosa, oral leukoplakia and oral submucous fibrosis were measured using an ocular micrometer disc. The nucleus:cytoplasm ratios in pathological cells were compared to age, sex and site matched controls. We found a significant reduction in the mean cytoplasmic and nuclear diameter in the experimental groups compared to normal controls. Methyl green-pyronin Y stained smears were clearer than Feulgen stained cells. We suggest that a decreased mean cytoplasmic diameter of exfoliated buccal mucosal cells could serve as an early indicator of dysplastic change in lesions that otherwise appear benign. Methyl green-pyronin Y may be useful for identifying premalignant and malignant transformations before a lesion is visible. The simplicity of the technique makes its routine use feasible.